ENHANCED RECOVERY AFTER SURGERY (ERAS) IN ONE ANASTOMOSIS GASTRIC BYPASS SURGERY: A MATCHED-COHORT STUDY - Aktimur, R.; Kirkil, C.; Yildirim, K.; Kutluer, N. (Springer, 2018)
[Abstract Not Available]
23rd World Congress of the International-Federation-for-the-Surgery-of-Obesity-and-Metabolic-Disorders (IFSO) -- SEP 26-29, 2018 -- Dubai, U ARAB EMIRATES